Effective techniques of memorizing the Quran: a study a Madrasah Tahfiz Al-quran, Terengganu,Malaysia - Ariffin, S.; Amir, S.; Abdullah, M.; Suliaman, I.; Ahmad, K.; Deraman, F.; Ahmad Shah, F.; Mohd Yusoff, Mohd Yakub @ Zulkifli; Abd Razzak, M.M.; Mohd Noor, M.M.; Touhami Meftah, J.; K. Kassar, A.; et al. (© IDOSI Publications, 2013, 2013)
Until today, memorization is still one of the methods used in the process of preservation of al-Qur’an.This article aims to review and analyze the methods and approaches used by a Centre of Tahfiz al-Qur’an, namely Madrasah Quran, Terengganu, Malaysia in the process to produce the students that can memorize the whole al-Qur’an. This study used the methods of documentation, observation and interviews in order to obtain the data. Through the analysis, this study found that there are four basic methods of memorizing al-Qur’an. The methods are Sabak method, Para Sabak, Ammokhtar and Halaqah Dauri. By using these four methods, the students could recite the whole Qur’an by memorization, within 15 hours without seeing the mushaf. These methods of memorization could be applied in all Quranic memorization centers in order to produce the huffaz who can fully remember the whole Qur’an.